VR/AR-BASED INTERACTIVE MULTIMEDIA CONTENT: A SYSTEMATIC REVIEW OF ITS IMPACT ON ENGAGEMENT AND LEARNING OUTCOMES IN THE AI ERA - Didik Cahyono; Rusiadi (CV. ADIBA AISHA AMIRA, 2026)
The development of Virtual Reality (VR) and Augmented Reality (AR) technologies integrated with artificial intelligence (AI) has opened up a new paradigm in interactive and adaptive immersive learning. This article presents a systematic review of the latest empirical evidence regarding the impact of VR/AR-based interactive multimedia content on learner engagement and learning outcomes in the AI era. The research findings indicate that VR/AR can enhance engagement across its three dimensions—cognitive, affective, and behavioural—through mechanisms such as a sense of presence, deep interactivity, and AI-facilitated adaptive personalisation. In terms of learning outcomes, VR/AR produces medium to large effect sizes (g = 0.50–0.85) on conceptual understanding, procedural skills, and knowledge transfer, particularly in domains requiring spatial visualisation and the simulation of complex procedures. The integration of AI reinforces these effects through adaptive learning pathways, real-time feedback, and precise learning analytics. However, this effectiveness is moderated by critical factors such as task type, students’ prior knowledge, duration of exposure, instructional design quality, and infrastructure readiness. In conclusion, the synergy between VR/AR and AI holds transformative potential for education, yet requires a holistic, pedagogy-based implementation approach that considers ethical and social sustainability aspects.